Singerocomus guadelupae (Boletaceae, Agaricomycetes): morphology and phylogeny reveal a widely distributed neotropical bolete discovered in Northeast Brazil - Andreza E. S. Peixoto; Erica S. Falcão; Anderlechi Barbosa-Silva; Ricardo Koroiva; Felipe Wartchow (Italian Journal of Mycology)
Singerocomus guadelupae is characterized by velutinous and red to pink pileus surface, cream to red or both colors mixed in stipe surface, unchanging white to cream pileus and stipe context, broadly ellipsoid inamyloid basidiospores, and fusoid to ventricose-rostrate cystidia. Morphological, molecular and phylogenetic analyses were performed on materials collected in Paraíba state, demonstrating that they belong to S. guadelupae with some characteristics not previously described for the species, suggesting a somewhat intraspecific phenotypic and phylogenetic plasticity. Also, it has a wide distribution, occurring from the Lesser Antilles towards South Brazil, and now is recorded for the first time from Northeast Brazil, in two conservation units from the state of Paraíba.